Superior immunogenicity of mRNA over adenoviral vectored COVID-19 vaccines reflects B cell dynamics independent of anti-vector immunity: Implications for future pandemic vaccines - Liu, Yi; Sánchez-Ovando, Stephany; Carolan, Louise; Dowson, Leslie; Khvorov, Arseniy; Jessica Hadiprodjo, A.; Tseng, Yeu Yang; Delahunty, Catherine; Khatami, Ameneh; Macnish, Marion; Dougherty, Sonia; Hagenauer, Michelle; et al. (Vaccine, 2023)
•vaccine induced higher Surrogate neutralizing antibody and RBD-targeted B cell responses were greater after mRNA compared to vector vaccine.•Although vector vaccine boosted antibodies against human Adenovirus, those titres did not correlate with anti-spike titres.•Further work is needed to improve the immunogenicity of vector vaccines as they remain an important option for pandemic and outbreak responses. Both vector and mRNA vaccines were an important part of the response to the COVID-19 pandemic and may be required in future outbreaks and pandemics. The aim of this study was to validate whether immunogenicity differs for adenoviral vectored (AdV) versus mRNA vaccines against SARS-CoV-2, and to investigate how anti-vector immunity and B cell dynamics modulate immunogenicity. We enrolled SARS-CoV-2 infection-naïve health care workers who had received two doses of either AdV AZD1222 (n = 184) or mRNA BNT162b2 vaccine (n = 274) between April and October 2021. Blood was collected at least once, 10–48 days after vaccine dose 2 for antibody and B cell analyses. Median ages were 42 and 39 years, for AdV and mRNA vaccinees, respectively. Surrogate virus neutralization test (sVNT) and spike binding antibody titres were a median of 4.2 and 2.2 times lower, respectively, for AdV compared to mRNA vaccinees (p < 0.001). Median percentages of memory B cells that recognized fluorescent-tagged spike and RBD were 2.9 and 8.3 times lower, respectively for AdV compared to mRNA vaccinees. Titres of IgG reactive with human adenovirus type 5 hexon protein rose a median of 2.2-fold after AdV vaccination but were not correlated with anti-spike antibody titres. Together the results show that mRNA induced substantially more sVNT antibody than AdV vaccine, which reflected greater B cell expansion and targeting of the RBD rather than an attenuating effect of anti-vector antibodies. ClinicalTrials.gov Identifier: NCT05110911.